Interactions Between Economic Field and Geographical Space: the Position of Hybrid Spaces (Andamios, Revista de Investigación Social, 2024)
A bourdieusian approach is proposed to understand the unequal relations among spaces, using the global animation industry as a case study. In this subfield there are two strategies: 1) high design, which refers to the production of audio-visual content through the most advanced techniques, and concentrated in dominant areas (United States of America); 2) mass animation, being India an example, whose role is that of dominated-dominant, and consists in exporting lower-cost content worldwide. Spaces such as Spain could be considered as hybrids: as they have not managed to develop the proper conditions to dominate one of the above strategies, they bear the structural inertia of the dominant spaces. The methodology consists in analysing key informant interviews and secondary sources.
Keywords: Bourdieu; hybrid; dominant; animation; space